Economic activities that depend on ichthyofauna in the North Pacific of Costa Rica - Villalobos-Rojas, Fresia (2014)
The North Pacific of Costa Rica is characterized by a large diversity of fish species. This diversity sustains two of the main economic activities developed there: fishing and tourism. We synthesized information from: semi-structured interviews with local stakeholders, biodiversity database from the Museo de Zoología, Universidad de Costa Rica, landings database from Costa Rican government (INCOPESCA) and the literature. A total of 424 fish species are reported from the area and the main target species for each fishery are: mahi-mahi, silky shark, hammerhead shark, tuna, sailfish, swordfish for longline fisheries; snappers, croakers, snook and groupers for artisanal fisheries; invertebrates and ornamental fish in dive-fisheries; shrimp in trawl fisheries; and wahoo, yellow-fin tuna, rooster fish, mahi-mahi, swordfish, sailfish, marlin in tourism fisheries. INCOPESCA does not take into account fishing effort but most species landings are decreasing, especially mahi-mahi, groupers and snappers. Conflicts between fisheries and tourism are arising due to competition for resources and over-exploitation. The main conflicts found were: (1) between sport and longline fisheries, (2) between recreational diving and dive-fisheries, (3) between the artisanal and shrimp trawling fisheries, and (4) among artisanal fishermen from different zones of the Pacific. These conflicts demonstrate the urgency of developing and effectively implementing management strategies that will guarantee the sustainability of fish resources in the area. Future studies should focus on generating information that will guide and support these management efforts. Rev. Biol. Trop. 62 (Suppl. 4): 119-138. Epub 2014 Diciembre 01.